REAKSI PASAR PADA REGULASI LOAN TO VALUE - Setiawan, Hendra; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
This research is used to determine the market reaction to the announcement of the regulation of the loan to value on the property sector companies in Indonesia Stock Exchange. The samples in this study used nonprobability sampling method with a saturation sampling technique ie 45 real estate companies. Data was collected through non-participant observation method. The data analysis technique used is the analysis of one sample t-test test and paired samples t-test was used where the observation period is for 7 days using the SPSS 21 software. Results of this research is that there is a significant market reaction to the announcement of the day to t-1, t-0, and t + 2 announcement regulatory loan to value. For paired samples t-test showed that there is no difference market reaction before and after the announcement regulatory loan to value.
Keywords: regulation of loan to value, market reaction, abnormal returns, the estimation period, the indonesia stock exchange